Acceptance Model of Web 2.0 Technology in self-learning: the perspective of TOE and STS - Dewi Lulu Widyasari, Yohana; Edi Nugroho, Lukito; Erna Permanasari, Adhistya (International Journal of Engineering and Technology, 2018)
The development of web 2.0 technology has an impact on the communication and collaboration processes carried out by its users. The use of social technology in the formal organizational environment and for formal needs is influenced by several factors. The TOE and STS aspects are used to understand the use of this technology for formal learning purposes that are carried out independently or self-learning. The TOE aspect is used to analyze technology components in relation to the organization and environment that uses it. The STS aspect is used to see the suitability of the technology to the task and its users including from the social side. Acceptance of social technology attached to web 2.0 technology by students by utilizing for the learning process need to be analyzed. The use of social media for the self-learning process shows that perceived behavior control does not significantly affect the intention of its users. User intention on social media in the self-learning process is influenced by the attitude and subjective norms of its users. The social influence brought by web 2.0 technology influences the subjective norms of its users. Â